Usefulness of Faecal Calprotectin Measurement in Children with Various Types of Inflammatory Bowel Disease - Marzena Komraus; Halina Wos; Sabina Wiecek; Maciej Kajor; Urszula Grzybowska-Chlebowczyk (Mediators of Inflammation)
Introduction. The aim of the study was to assess the usefulness of the FC measurement in children with various types of IBD and relation to the disease activity. Patients and Methods. 91 patients (49 boys: 53.85% and 42 girls: 46.15%, mean age: 13.38 years, range 6–18 years) were included in the analysis. Patients were divided into the groups: B1—24 children with CD, B2—16 patients with UC, and a group comprising 31 children with other types of colitis; the control group (K) comprised 20 healthy children. FC was assayed by ELISA method, using Phical test (Calpro). Results. The mean faecal calprotectin concentrations were higher in children with CD and UC as compared to healthy controls, patients with eosinophilic, lymphocytic, and nonspecific colitis. A positive correlation was observed between FC concentrations and the disease activity (the PCDAI scale, the Truelove-Witts Scale, and the endoscopic Rachmilewitz Index). Conclusion. It seems that the FC concentrations can be a useful, safe, and noninvasive test in children suspected for IBD, since FC concentration is higher in children with CD and UC than in patients with other inflammatory diseases.